ADVANTAGES AND DISADVANTAGES OF INTERACTIVE METHODS INTRODUCING THE СLT (СOMMUNIСATIVE LANGUAGE TEACHING) APPROACH (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The article highlights the main priorities of using advantages and disadvantages of interactive methods of the сommuniсative language teaching approach as an alternative method of developing the intercultural communication competence of cadets through teaching English. The author considers this approach to be one of the most effective and good results.